MODEL PEMBELAJARAN KOOPERATIF TEAM GAMES TOURNAMENT DAPAT MENINGKATKAN MOTIVASI PEMBELAJARAN BOLA BASKET DI KELAS X IPA 1 SMAN 1 CILIMUS - Avip Muhamad Sidik (STKIP Muhammadiyah Kuningan, 2023)
Avip Muhamad Sidik (NIM: 182223126), This study aims to increase student motivation in learning basketball at SMAN 1 Cilimus through the Team Game Tournament method. This research is an experimental research conducted for 3 meetings. In June 2022. The population is student of x ipa 1 SMAN 1 Cilimus 36 people. The results showed that the Team Game Tournament method was very suitable to be applied by class X IPA 1 students of SMAN 1 Cilimus. Because with the Team Game Tournament program, students can increase motivation and enthusiasm in learning basketball. The conclusion is that Team Game Tournament can increase students' learning motivation. Keywords : Team Game Tournament, Basketball